SYNERGY OF PRODUCT QUALITY AND AUTOMATIC TELLER MACHINE (ATM) SERVICES OF BANK KALTENG IN INCREASING CONSUMER SATISFACTION : (A Study of Student Members of the Accounting Department Association for the 2023/2024 Period at the Faculty of Economics and Business, Palangka Raya University) - Elpan Pino’o (KENDALI: Economics and Social Humanities, 2025)
This study aims to comprehensively analyze the influence of product quality and service quality of Bank Kalteng Automated Teller Machine (ATM) services on consumer satisfaction, focusing on student members of the Accounting Department Association at the Faculty of Economics and Business, University of Palangka Raya, during the 2023/2024 period. The research adopts a quantitative approach, utilizing a structured questionnaire distributed to a sample of 60 respondents selected through the Slovin formula from a population of 70 students. Multiple linear regression analysis, supported by classical assumption tests, was employed to examine the simultaneous and partial effects of product quality (X1) and service quality (X2) on consumer satisfaction (Y). The results indicate that, when analyzed together, both product quality and service quality have a positive and significant effect on consumer satisfaction. However, when tested partially, only service quality demonstrates a positive and statistically significant influence, while product quality, although positive, does not show a significant effect. The model explains 27.15% of the variation in consumer satisfaction, suggesting that other factors may also play a role in shaping satisfaction levels. These findings highlight the crucial importance of service quality in the context of ATM banking services, especially for young and educated consumers such as university students, who often have high expectations for convenience, reliability, and responsiveness. The practical implication of this research is that Bank Kalteng should prioritize continuous improvement in service quality, including staff training, technological upgrades, and responsiveness to consumer needs, to enhance satisfaction and loyalty. Furthermore, the study provides valuable insights for other banks facing similar challenges in the digital era, emphasizing that while product features are important, the quality of service delivery remains the main determinant of customer satisfaction in ATM services. Future research is encouraged to explore additional variables that may affect satisfaction, such as security, accessibility, and digital integration.